Handbook of adhesives - Skeist, Irving (Reinhold Publishing Corporation, 1962)
Adhesives are indispensable. They are required pling agents, and other key ingredients. Special in myriad products-aircraft and abrasives, cars attention is given to such flourishing categories and cartons, shoes and safety glass, tape and as acrylics, anaerobics, cyanoacrylates, poly urethanes, epoxy resins, polyvinyl acetate, high tires. This Third Edition of Handbook of Ad hesives, like the 1962 and 1977 editions, seeks temperature adhesives, hot melts, silicones, and to provide the knowledge needed for optimum silanes. selection, preparation, and utilization of adhe The last 14 chapters, on adherends and bond sives and sealants. The information is detailed ing technology, involve the auto industry, air and explicit, with several hundred illustrative craft, electronics, the bonding of wood, formulations. textiles, rubber and plastics, construction, ab Expert information has been supplied in 47 rasives, pressure-sensitives, nonwovens, and chapters written by 70 industry specialists, pro sealants. Mechanical handling of two-compo fessors, and consultants. Five chapters on fun nent systems is examined. The concluding damentals provide the theoretical and economic chapter highlights the exciting progress that is underpinnings-why adhesives work, how they being made in the use of robotics to apply ad are selected, how the surface is prepared, how hesives, techniques already far advanced in au they are applied, how they are set, how the tomotive assembly. cured joint is tested.